2022
DOI: 10.1136/jitc-2022-004859
|View full text |Cite
|
Sign up to set email alerts
|

BND-22, a first-in-class humanized ILT2-blocking antibody, promotes antitumor immunity and tumor regression

Abstract: BackgroundCancer immunotherapy has revolutionized cancer treatment. However, considering the limited success of immunotherapy to only some cancer types and patient cohorts, there is an unmet need for developing new treatments that will result in higher response rates in patients with cancer. Immunoglobulin-like transcript 2 (ILT2), a LILRB family member, is an inhibitory receptor expressed on a variety of immune cells including T cells, natural killer (NK) cells and different myeloid cells. In the tumor microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…For instance, MK4830 is an antibody in early phase clinical development targeting the HLA-G receptor, ITL4. In the early phase I study signs of activity were reported in PD-1 pretreated patients ( 51 ) Other studies evaluating antibodies targeting ITL2 such as BND22 are in preclinical and early clinical development ( 12 , 52 ). Early signs of clinical activity have been reported in microsatellite instability-high (MSH-I) colorectal tumors and ovarian cancer, among other tumor types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, MK4830 is an antibody in early phase clinical development targeting the HLA-G receptor, ITL4. In the early phase I study signs of activity were reported in PD-1 pretreated patients ( 51 ) Other studies evaluating antibodies targeting ITL2 such as BND22 are in preclinical and early clinical development ( 12 , 52 ). Early signs of clinical activity have been reported in microsatellite instability-high (MSH-I) colorectal tumors and ovarian cancer, among other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently agents targeting HLA-G or their receptors, such as the LILRB family of proteins have shown preclinical activity, and some of these agents have transitioned to clinical testing ( 11 , 12 ). These drugs predominantly act on myeloid derived suppressor cells ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The commercial availability of the semiautomated FOX system could hasten the implementation of HRPF experiments at worldwide mass spectrometry facilities. The use of FOX for protein footprinting has been demonstrated for determining the epitope of TNFα recognized by the adalimumab antibody and measuring the effect of post-translational modifications in a dynamic system like ovalbumin. , Until now, the FOX system applications have been “ in vitro ” protein footprinting experiments in comparison to synchrotron X-rays and FPOP HRPF platforms, which have addressed a wide variety of structural biology questions for diverse macromolecules. ,,,, The FOX system has the capability to address more challenging questions in future which range from “ in-cell ” protein footprinting to membrane proteins. ,, We envision that this benchmarking of the FOX protein oxidation system in comparison to synchrotron X-rays under physiological pH and scavenging conditions will spur the adoption of the FOX system’s HRPF applications and advance the HRPF field worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…HRPF is an umbrella term for covalent labeling approaches employing •OH adducts, where the •OH can be generated by a variety of approaches: radiolysis of water by X-rays, γ-rays, electron beams, electric discharges or plasma sources; decomposition of hydrogen peroxide (H 2 O 2 ) using transition metal-based Fenton chemistry; and photolysis of H 2 O 2 using lasers (FPOP) or a high-pressure flash oxidation lamp. Among these •OH sources, high-intensity X-ray synchrotron beamlines played an essential role in the beginning of the HRPF field and continue to be important resources for HRPF method development and applications. X-ray beamlines deliver a measurable, reproducible, and controlled •OH dose on microsecond to millisecond (and longer) time scales. The availability of a high •OH dose at synchrotron beamlines for the structural biology community has allowed studies of complex and highly scavenging systems such as virus assembly, neurodegenerative diseases, epitope mapping, and time-resolved macromolecular dynamics. Until now, MS analysis steps for X-ray irradiated samples have been carried out at geographically distant sites from the synchrotron, resulting in a slow feedback loop between sample chemistry optimization, beamline experiments, and data analysis . The availability of a benchtop •OH labeling setup for MS facilities in conjunction with MS access at synchrotron X-ray beamlines could and should accelerate the wider adoption of HRPF technology by the structural biology community.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of ILT to HLA-G can inhibit the cytokine secretion, cell differentiation, and cell proliferation of immune cells, and induce cytotoxicity and apoptosis [115]. For example, after ILT4 binds to HLA-G, it can recruit SHP-1/-2 and activate the nuclear factor-κ-gene binding (NF-κB) pathway, leading to the increase in Interleukin-6 (IL-6) level and then the activation of the STAT3 pathway, which affects the function and maturation of DCs and leads to impaired innate immunity [120].…”
Section: Hla-g Dimerizationmentioning
confidence: 99%